Extraordinary enhancement of nonlinear optical interaction in NbOBr2 microcavities - Chen, Wenduo (2024)
2D materials are burgeoning as promising candidates for investigating nonlinear optical effects due to high nonlinear susceptibilities, broadband optical response, and tunable nonlinearity. However, most 2D materials suffer from poor nonlinear conversion efficiencies, resulting from reduced light-matter interactions and lack of phase matching at atomic thicknesses. Herein, a new 2D nonlinear material, niobium oxide dibromide (NbOBr2) is reported, featuring strong and anisotropic optical nonlinearities with scalable nonlinear intensity. Furthermore, Fabry-Pérot (F-P) microcavities are constructed by coupling NbOBr2 with air holes in silicon. Remarkable enhancement factors of ≈630 times in second harmonic generation (SHG) and 210 times in third harmonic generation (THG) are achieved on cavity at the resonance wavelength of 1500 nm. Notably, the cavity enhancement effect exhibits strong anisotropic feature tunable with pump wavelength, owing to the robust optical birefringence of NbOBr2. The ratio of the enhancement factor along the b- and c-axis of NbOBr2 reaches 2.43 and 5.27 for SHG and THG at 1500 nm pump, respectively, which leads to an extraordinarily high SHG anisotropic ratio of 17.82 and a 10° rotation of THG polarization. The research presents a feasible and practical strategy for developing high-efficiency and low-power-pumped on-chip nonlinear optical devices with tunable anisotropy.